Perspectives on the future of recycled water in California: results from interviews with water management professionals. Issue 11 (19th September 2019) - Sokolow, Sharona; Godwin, Hilary; Cole, Brian L.
Abstract : Expanded use of recycled water has potential to improve the sustainability of water systems in areas with high water insecurity. Despite this, rates of recycled water use in California remain low. To identify barriers to expansion of recycled water use in California, we conducted open-ended interviews with a targeted sample of 12 stakeholders representing a range of viewpoints among individuals familiar with urban water management operations in California, including experts from government regulatory and public health agencies, wastewater suppliers, independent consultants, and engineers. Barriers identified by respondents related to regulations, infrastructure, funding, technology, health risks, and public perceptions. Respondents provided concrete suggestions for how to lower these barriers and insights into the roles that public health professionals could play in this effort. This work suggests that public health professionals can play a critical role in facilitating the expanded use of recycled water and improving water security and sustainability worldwide.